Influence of Information Quality on Retailer Satisfaction through Supply Chain Flexibility and Supplier Relationship Management in the Retail Industry - Putra, Ardiono; Tarigan, Zeplin Jiwa Husada; Siagian, Hotlan (Jurnal Teknik Industri: Jurnal Keilmuan dan Aplikasi Teknik Industri, 2020)
Businesses always compete to improve customer satisfaction. A firm engaged in as a distributor as well, always try to provide satisfaction to their customer, in this case, retailer and wholesales. The distributor can improve retailer satisfaction by providing such information that suits retailer requirements in the pursuit that the supply chain flow can move quickly, particularly on the flow of products from the manufacturing ordered by the distributors. This study aims to obtain a relationship between distributors and retailer companies. This study surveyed 100 retailers, and wholesale companies engaged in Fast Moving Consumer Goods (FMCG) and the supplier domiciled in the city of Makassar, South Sulawesi, with revenues of more than IDR 300,000,000. - / year. SmartPLS software version 2.0 was used to test the hypothesis. The results of the study found that information quality can provide a positive increase in improving supplier relationship management. Adequate information quality cannot significantly increase supply chain flexibility and retailer satisfaction. Supplier relationship management built by distributors can have an impact of 0.611 on supply chain flexibility in retail and retail satisfaction companies of 0.367. The stronger distributor and retailer relationship can increase distributor flexibility and retail satisfaction. Supply chain flexibility built by distributor companies can have a significant impact on retailer satisfaction of 0.463. This research provides an improvement in the development of supply chain management theory, in particular, building relationships with customers.